Gonadal dysgenesis in Turner syndrome with Y-chromosome mosaicism: Two case reports - Leng, Xue-Fei (World J Clin Cases, 2020)
BACKGROUND: Turner syndrome (TS) has a variety of different karyotypes, with a wide range of phenotypic features, but the specific karyotype may not always predict the phenotype. TS with Y chromosome mosaicism may have mixed gonadal dysgenesis, and the mosaicism is related to the potential for gonadoblastoma. CASE SUMMARY: In this case report, we report two cases of TS with different karyotypes and gonadal dysgenesis. Patient 1 had obvious virilization, and was positive for the SRY gene, but her karyotype in peripheral blood lymphocytes was 45X. Patient 2 had a mosaic karyotype, 45X/46X, dic (Y:Y) (p11.3:p11.2), and the proportion of Y-bearing cells was 50% in peripheral blood lymphocytes, but the patient had normal female external genitalia and streaky gonads, with no genital virilism. Different tissues in the same TS individual may exhibit different ratios of mosaicism. The gonadal determination and differentiation of mosaic TS are primarily dependent on the predominant cell line in the gonads. CONCLUSION: In TS patients with virilization, it is necessary to test at least two to three tissues to search for cryptic Y material.